2011
DOI: 10.4103/0255-0857.83917
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the boronic acid disk potentiation test and cefepime–clavulanic acid method for the detection of ESBL among AmpC-producing Enterobacteriaceae

Abstract: The use of boronic acid in disk diffusion testing along with the CLSI described PCT enhances ESBL detection in the presence of AmpC betalactamases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…Among 259 clinical isolates of Enterobacteriaceae , 68 (26.25%) and 14(5.4%) were pure ESBL and AmpC producers respectively; 53 (20.46%) isolates were combined ESBL and AmpC producers; and 124 (47.87%) of the isolates did not harbor any type of enzyme (Table 1). In our study the prevalence of ESBL and AmpC co- producing isolates was 20.46%, which is relatively low (27.5% and 33.7%) compared to the previous report [25, 26]. This variation may be due to different pattern of antibiotic use and differences in the study group.…”
Section: Resultscontrasting
confidence: 62%
“…Among 259 clinical isolates of Enterobacteriaceae , 68 (26.25%) and 14(5.4%) were pure ESBL and AmpC producers respectively; 53 (20.46%) isolates were combined ESBL and AmpC producers; and 124 (47.87%) of the isolates did not harbor any type of enzyme (Table 1). In our study the prevalence of ESBL and AmpC co- producing isolates was 20.46%, which is relatively low (27.5% and 33.7%) compared to the previous report [25, 26]. This variation may be due to different pattern of antibiotic use and differences in the study group.…”
Section: Resultscontrasting
confidence: 62%
“…In our study, we found 64.50% isolates to be pure ESBL producers and 12.70% isolates to be pure AmpC producers and 8.39% were ESBL + AmpC coproducers. Shoorashetty et al reported 6% and 41% isolates to be pure AmpC and pure ESBL producers, respectively, with 27.5% isolates to be AmpC and ESBL coproducers [18]. Bakthavatchalu et al reported 5.4% and 26.25% pure AmpC and pure ESBL producers, respectively, with 20.46% AmpC and ESBL coproducers [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, β-lactamase-producing Enterobacteriaceae are commonly cross-resistant to other classes of antibiotics, such as fluoroquinolones, trimethoprim/sulfamethoxazole, and aminoglycosides, which results in limited therapeutic options to treat infections caused by these pathogens [3]. Extended-spectrum β-lactamase (ESBL) and AmpC β-lactamase are important mechanisms of beta-lactam resistance among Enterobacteriaceae [5]. Carbapenemases are β-lactamases and able to hydrolize β-lactam antibiotics, including carbapenems and also become a significant resistance mechanism in Enterobacteriaceae [6].…”
Section: Introductionmentioning
confidence: 99%